DEVELOPMENT OF THE ETHOSTAT EDUCATIONAL GAME (STATISTICAL ETHNOMATHEMATICS) WITH THE AID OF CONSTRUCT 2 SMK: DEVELOPMENT OF THE ETHOSTAT EDUCATIONAL GAME (STATISTICAL ETHNOMATHEMATICS) WITH THE AID OF CONSTRUCT 2 SMK - Indra Prayoga (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this study is to develop Ethostat as an ethnomathematics-based educational game for learning statistics, supported by Construct 2. This research employed the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Disseminate). The research subjects were students of class X TF C at SMK Ma'arif NU 2 Ajibarang. Data collection techniques included observation, interviews, and questionnaires. The instruments used were the media validation questionnaire, the material validation questionnaire, and the student response questionnaire. Data analysis techniques involved product validity and practicality tests. The research results are as follows: 1) The media validation test by experts yielded a percentage of 83.5%, categorized as very valid, and the material validation scored 94%, also categorized as very valid. 2) The practicality test by users obtained a percentage of 83.7%, which falls into the practical category. Based on these results, Ethostat is considered feasible to be used as a valid and practical media for learning